2008
DOI: 10.1016/j.cub.2008.05.043
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Bimodal Looming Signals through Neuronal Coherence in the Temporal Lobe

Abstract: The ability to integrate information across multiple sensory systems offers several behavioral advantages, from quicker reaction times and more accurate responses to better detection and more robust learning. At the neural level, multisensory integration requires large-scale interactions between different brain regions--the convergence of information from separate sensory modalities, represented by distinct neuronal populations. The interactions between these neuronal populations must be fast and flexible, so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
99
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(115 citation statements)
references
References 38 publications
16
99
0
Order By: Relevance
“…In audiovisual processing, this law suggests that redundant information from an irrelevant modality can benefit the perception of the target signal to the extent that the target signal is weak in the first place. Previous studies have shown that sounds with rising amplitude evoke greater neural responses than do falling sounds (Maier, Chandrasekaran & Ghazanfar, 2008;Maier & Ghazanfar, 2007), consistent with our finding of faster and more accurate detection of rising sounds across conditions. Given that processing of falling sounds was relatively inferior to processing of rising sounds, inverse effectiveness would predict a greater facilitation of detection for falling sounds when congruent cross-modal cues are available.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In audiovisual processing, this law suggests that redundant information from an irrelevant modality can benefit the perception of the target signal to the extent that the target signal is weak in the first place. Previous studies have shown that sounds with rising amplitude evoke greater neural responses than do falling sounds (Maier, Chandrasekaran & Ghazanfar, 2008;Maier & Ghazanfar, 2007), consistent with our finding of faster and more accurate detection of rising sounds across conditions. Given that processing of falling sounds was relatively inferior to processing of rising sounds, inverse effectiveness would predict a greater facilitation of detection for falling sounds when congruent cross-modal cues are available.…”
Section: Discussionsupporting
confidence: 92%
“…Looming sounds (typically, an increase in amplitude) can serve as a warning of impending contact (Bach, Schachinger, Neuhoff, Esposito, Di Salle, Lehmann & Seifritz, 2008;Ghazanfar, Neuhoff & Logothetis, 2002) and are more likely to speed up responses, bias attention and change distance estimates (Ghazanfar et al, 2002;Maier et al, 2004;Neuhoff, 1998Neuhoff, , 2001, and induce stronger neural activation than are receding or constant sounds (Bach et al, 2008;Maier et al, 2008;Maier & Ghazanfar, 2007;Seifritz et al, 2002). Although frequency spectrum, reverberant energy, and interaural differences also vary with sound motion in depth (Hall & Moore, 2003;Zahorik, 2002), modulating sound amplitude is sufficient to produce the response biases associated with looming sounds (Bach, Neuhoff, Perrig & Seifritz, 2009) and activate cortical areas known to respond to auditory motion (Seifritz, Neuhoff, Bilecen, Scheffler, Mustovic, Schachinger & Di Salle, 2002).…”
Section: Audiovisual Motion In Depthmentioning
confidence: 99%
“…Multisensory stimulation appears to result in more extensive functional coupling between primary auditory and visual cortices as well as pSTS. Similar findings have been reported in studies of macaque monkeys Maier et al, 2008;. Recordings in these studies were limited to auditory regions and STS (no electrodes were implanted in visual cortices), Nonetheless, these studies showed there to be functional coupling between auditory cortex and the STS in the theta and beta frequency bands of the local field potential as well as between auditory belt regions and the STS at higher gamma frequencies above 50 Hz Maier et al, 2008).…”
Section: Source Estimationssupporting
confidence: 81%
“…These results add to the growing body of literature on coding stimulus attributes by assignment to different oscillatory phases (15)(16)(17)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) (16). Much of the existing literature focuses on invertebrate and hippocampal circuits, demonstrating proof of coding principle; however, more recently phase coding has been observed in V1 for visual stimuli (15,16) and in the prefrontal cortex (PFC) for item order during working memory (17).…”
Section: Discussionmentioning
confidence: 57%